An electrocatalyst material for producing hydrogen peroxide by oxygen reduction and its preparation and application

By combining MoS2/Fe porous conductive particles with polymer composite precursors and preparing electrocatalyst materials using microwave radiation and freeze-drying technology, the problem of low activity of existing electrocatalyst materials is solved, efficient hydrogen peroxide production is achieved, and the water treatment effect is significantly improved.

CN119461592BActive Publication Date: 2025-03-28SHAANXI UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510025460.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-03-28
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

The existing electrocatalyst materials have low activity in redox reactions, resulting in limited concentration of hydrogen peroxide generated in situ, which is difficult to meet the needs of efficient water treatment.

Method used

MoS2/Fe porous conductive particles are combined with polymer composite precursors to prepare an electrocatalyst material for oxygen reduction in situ hydrogen peroxide production through microwave radiation and ultra-low temperature freeze-drying technology.

Benefits of technology

It significantly improves the efficiency of the catalytic reaction of oxygen reduction to produce H2O2, improves the effect of advanced oxidation water treatment technology of hydrogen peroxide, and maintains stable catalytic activity, which is suitable for multiple reuses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461592B_ABST
    Figure CN119461592B_ABST
Patent Text Reader

Abstract

The present invention discloses an electrocatalyst material for in-situ production of hydrogen peroxide by oxygen reduction, and a preparation method and application thereof, which belong to the field of organic wastewater treatment. MoS2 / Fe porous conductive particles and high molecular polymers are used as main components, and ethylene glycol oxalate and polyacrylamide are combined as dispersing auxiliary solvents and pore-forming agents to form a three-dimensional composite conductive catalyst material; through ultra-low temperature freeze drying and microwave radiation technology, the material structure is optimized, the catalytic reaction active sites are increased, and efficient electrocatalytic oxygen reduction in-situ production of hydrogen peroxide is achieved; MoS2 / Fe porous conductive particles not only optimize the catalyst performance, but also achieve high-value utilization of solid waste; the electrocatalyst material has excellent conductivity, catalytic activity and organic wastewater degradation ability, and the removal effect is stable before and after use, and it can be reused many times, which reduces the use cost and provides broad application prospects in the fields of environmental protection and energy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of organic wastewater treatment, in particular to an advanced oxidation water treatment technology, and in particular to an electrocatalyst material for in-situ production of hydrogen peroxide by oxygen reduction, and the preparation and application thereof. Background Art

[0002] In the field of advanced oxidation water treatment, hydrogen peroxide-based water treatment technologies have attracted much attention due to their ability to efficiently degrade organic matter, such as Fenton oxidation (Fe(II) / H2O2), ozone catalysis (O3 / H2O 2) , UV / H2O2, and other technologies. However, the strong corrosiveness and transportation risks of hydrogen peroxide in traditional technologies limit its widespread application and increase operating and management costs. In order to overcome these challenges, electrochemical in-situ hydrogen peroxide generation technology came into being. It reduces the oxygen in the system to produce hydrogen peroxide by electrochemical methods, and has successively developed advanced oxidation water treatment processes based on hydrogen peroxide such as electro-Fenton and hydrogen peroxide-ozone. Compared with the traditional treatment method of adding hydrogen peroxide, the electrochemical in-situ method generates hydrogen peroxide in situ through electrocatalyst materials, saving the cost of transportation and storage. More importantly, the continuous generation of hydrogen peroxide in the electrochemical system has significantly improved the removal effect and rate of organic pollutants compared with traditional technologies. Advanced oxidation processes such as electro-Fenton and hydrogen peroxide-ozone benefit from this.

[0003] Although electrochemical in-situ hydrogen peroxide generation technology has made some progress, existing electrocatalyst materials still have serious defects. Carbon-based materials such as activated carbon fiber, carbon felt and graphite felt have become the most commonly used electrocatalyst materials for hydrogen peroxide production due to their good conductivity, stability and corrosion resistance. However, due to their low redox reaction activity, the concentration of in-situ hydrogen peroxide generation is limited, which to some extent limits the promotion and application of this technology in the field of advanced oxidation water treatment. Summary of the invention

[0004] In view of the technical problem that in the electrochemical in situ hydrogen peroxide production technology, the redox reaction activity of existing materials is relatively low, resulting in a limited concentration of hydrogen peroxide produced in situ, which is difficult to meet the needs of efficient water treatment. The present invention provides an electrocatalyst material, preparation and application for in situ hydrogen peroxide production by oxygen reduction, which solves the problem of insufficient concentration of hydrogen peroxide produced by oxygen reduction and effectively improves the effect of hydrogen peroxide advanced oxidation water treatment technology.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] The present invention provides a method for preparing an electrocatalyst material for in-situ production of hydrogen peroxide by oxygen reduction, comprising:

[0007] S1, preparation of MoS2 / Fe porous conductive particles;

[0008] S2, mixing MoS2 / Fe porous conductive particles, polydimethylsiloxane (PDMS) and ethylene glycol oxalate to obtain a polymer composite precursor;

[0009] S3, adding polyacrylamide and polytetrafluoroethylene to the polymer composite precursor, heating, and ultrasonic treatment to obtain a microemulsion;

[0010] S4, the microemulsion is subjected to microwave irradiation and freeze-drying in sequence to obtain an electrocatalyst material for in-situ production of hydrogen peroxide by oxygen reduction.

[0011] In S1, the preparation of MoS2 / Fe porous conductive particles includes: dissolving and mixing ammonium molybdate and sublimated sulfur, adding a nitrogen source, a reducing agent and blast furnace slag, placing the mixture in a reactor for reaction, centrifuging, drying and calcining to obtain MoS2 / Fe porous conductive particles; the nitrogen source is any one of urea, ammonium salt and nitrate, and the reducing agent is any one of ascorbic acid, hydroxylamine hydrochloride and sodium citrate.

[0012] The mass ratio of the ammonium molybdate to the sublimated sulfur, the nitrogen source, the reducing agent and the blast furnace slag is 0.2-0.6:1-5:3-5:0.5-3.5:2-10.

[0013] Furthermore, the nitrogen source is urea, and the reducing agent is ascorbic acid.

[0014] The reaction temperature is 100°C to 140°C, the reaction time is 2 h to 5 h, and the reaction pressure is 2 MPa to 6 MPa; the calcination temperature is 400°C to 600°C, and the calcination time is 1 h to 3 h.

[0015] Furthermore, the calcination adopts a tube furnace with a heating program of: a rate of 10°C / min and a N2 flow rate of 20mL / min.

[0016] In S2, the mass ratio of the MoS2 / Fe porous conductive particles, polydimethylsiloxane and ethylene glycol oxalate is 1~3:1~3:1~6.

[0017] In S3, the volume ratio of the polyacrylamide, polytetrafluoroethylene and polymer composite material precursor is 1-3:1-5:1-6, the heating temperature is 40°C-80°C, and the ultrasonic treatment is 10 min-40 min.

[0018] Furthermore, the mass fraction of the polyacrylamide is 1‰~5‰.

[0019] Furthermore, the mass fraction of polytetrafluoroethylene is 20% to 60%.

[0020] In S4, microwave drying is carried out under the conditions of Ar gas flow rate of 5 L / min~20 L / min, microwave power of 500 W~1500 W, and temperature of 80 ℃~150 ℃ for 0.5 h~2 h.

[0021] In S4, the freeze-drying conditions are: 500 W~1200 W, freeze-drying at -20℃~-10℃ for 10 min~20 min.

[0022] The electrocatalyst material for in-situ production of hydrogen peroxide by oxygen reduction is prepared by the above-mentioned preparation method.

[0023] The specific surface area of ​​the electrocatalyst material for in-situ production of hydrogen peroxide by oxygen reduction is 1800-3200 g / cm 2 The hydrophilic angle is 60°~80°, the porosity is 75%~90%, the average pore size is 0.14 μm~3.5 μm, and the pore volume is 0.15 g / cm 3 ~0.65g / cm 3 .

[0024] The application of the electrocatalyst material for in-situ production of hydrogen peroxide by oxygen reduction in the degradation of organic wastewater, wherein the electrocatalyst material for in-situ production of hydrogen peroxide by oxygen reduction is used as a cathode.

[0025] Compared with the prior art, the present invention achieves the following technical effects:

[0026] The invention provides a method for preparing an electrocatalyst material for in-situ production of hydrogen peroxide by oxygen reduction, and proposes a new electrocatalyst material and a preparation method thereof. The method adopts conductive particles with extremely low resistance and a polymer composite material precursor with good plasticity as main components to form the basis of a three-dimensional composite conductive catalyst material, which provides the possibility for efficient in-situ production of hydrogen peroxide by electrocatalytic oxygen reduction. Ethylene glycol oxalate (dispersant) and polyacrylamide (PAM) are innovatively used as dispersing auxiliary solvents and pore-forming agents to ensure uniform dispersion of the conductive particles without damaging the particle surface. The low boiling point and high volatility of ethylene glycol oxalate ensure complete removal of the solvent during the preparation of the composite material.

[0027] By utilizing the PAM cross-linked filamentary structure, the dispersant vapor and carbon gas layer formed during the heating process are "retained" in situ in the PDMS, so that the deposition process of the nanoscale active catalytic layer formed by the conductive particles on the PDMS surface and inside the filamentary cross-linking can be efficiently realized and the load is uniform; microwave radiation and ultra-low temperature freeze-drying technology are used to achieve integrated heating and freeze-drying, improve the spatial reaction cross-linking and fiber microchannel structure of the material, and the special effect of the microwave electromagnetic field cooperates with its special drying method to increase the active sites of the catalytic reaction and improve the efficiency of the oxygen reduction catalytic reaction to produce H2O2.

[0028] Furthermore, MoS2 / Fe porous conductive particles are prepared through a specific combination of ammonium molybdate, urea, ascorbic acid and blast furnace slag, and have excellent conductivity and catalytic activity; utilizing the high specific surface area and excellent conductivity of blast furnace slag, not only the preparation and surface morphology of the catalyst material are optimized, but also the high-value utilization of solid waste is achieved.

[0029] Furthermore, during the preparation process, the polymer composite precursor can form a stable structure, providing the necessary support for the subsequent catalytic reaction, helping to maintain the morphology and structural stability of the catalyst, preventing agglomeration or deformation during the reaction, thereby ensuring the continuous and efficient progress of the catalytic reaction; it can act as a dispersant to promote the uniform dispersion of conductive particles (such as MoS2 / Fe porous conductive particles) in the material, helping to increase the contact area between the conductive particles and the reactants, and improving the efficiency of the catalytic reaction; at the same time, its special structure also provides more electron transfer space and electrocatalytic active sites for electrochemical reactions, thereby improving the rate and efficiency of the catalytic reaction.

[0030] The electrocatalyst material for in-situ production of hydrogen peroxide by oxygen reduction provided by the present invention is composed of MoS2 / Fe porous conductive particles and an electrocatalytic active layer supported on a polymer composite material precursor. The material not only has excellent conductivity and catalytic activity, but also provides more electron transfer space and electrocatalytic active sites through the support and stabilization of the polymer composite material precursor, thereby significantly improving the efficiency of electrocatalytic oxygen reduction to produce H2O2; not only can H2O2 be efficiently produced, but also the oxidizing property of H2O2 can be utilized to degrade pollutants in organic wastewater, and the material also has the ability to degrade organic wastewater, which is helpful for environmental protection and wastewater treatment; during use, the material can maintain stable catalytic activity without obvious performance degradation, which is conducive to repeated use and reduces the cost of use.

[0031] The electrocatalyst material for in-situ production of hydrogen peroxide by oxygen reduction provided by the present invention is used in the degradation of organic wastewater. The contact angle of the electrocatalyst material prepared by the present invention is only 65 degrees, which is much lower than the contact angles of traditional carbon-based electrocatalyst materials (such as activated carbon fiber and graphite felt) (125 degrees and 130 degrees, respectively), indicating that it has better hydrophilicity, which is beneficial to the mass transfer efficiency between oxygen in the solution and the electrocatalyst material during the reaction process, thereby improving the efficiency of oxygen reduction to produce H2O2; the electrocatalyst material prepared by the present invention can produce 1142 H2O2 within a two-hour reaction time. mg / L, which is 10-20 times the output of traditional carbon-based electrocatalyst materials, which means that in the process of organic wastewater treatment, more effective oxidants can be provided, thereby improving the treatment efficiency and effect; the electrocatalyst cathode material prepared by the present invention treats organic wastewater and achieves a COD removal rate of 98%, which is much higher than the COD removal rate of traditional carbon-based cathode materials (only 18.5%), indicating that the material of the present invention has significant advantages in removing COD from organic wastewater, and the treatment efficiency is much higher than that of traditional materials; the performance can be kept stable in 9 consecutive wastewater treatment experiments without obvious performance degradation, indicating that the material has good stability and durability, and can treat organic wastewater efficiently for a long time; it can be seen that the electrocatalyst material for in-situ production of hydrogen peroxide by oxygen reduction provided by the present invention is efficient, stable and reusable, and has extremely high practical value and industrial promotion potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The electron microscope scanning image of the surface of the electrocatalyst material prepared by the present invention; wherein A is the electron microscope scanning image of the surface of the electrocatalyst material; B is the enlarged image of the attachment on the cross-linked filament;

[0033] Figure 2 This is a physical picture of the preparation of electrocatalyst materials in Example 1 of the present invention;

[0034] Figure 3 Preparation of electrocatalyst materials and hydrophilicity tests of activated carbon fibers and graphite felt for Example 1 of the present invention;

[0035] Figure 4 A comparison chart of hydrogen peroxide production between the electrocatalytic material prepared in Example 2 of the present invention and commercial traditional carbon-based materials;

[0036] Figure 5 This is a diagram showing the effect of preparing electrocatalyst materials for treating organic wastewater according to Example 3 of the present invention;

[0037] Figure 6 A comparison chart of continuous operation capability tests of the electrocatalyst material prepared in Example 3 of the present invention and commercial graphite felt material. DETAILED DESCRIPTION

[0038] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0039] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0040] In the present invention, unless otherwise specified, all experimental raw materials used are commercially available products well known to those skilled in the art. The blast furnace slag used in the present invention is solid waste discharged by a certain ironmaking company in Liaoning.

[0041] 1. Specific implementation cases

[0042] Example 1

[0043] This embodiment provides an electrocatalyst material for in-situ production of hydrogen peroxide by oxygen reduction, and the specific preparation process is as follows:

[0044] 1. Preparation of MoS2 / Fe porous conductive particles

[0045] 196 mg of ammonium molybdate was dispersed in 50 mL of deionized water, stirred for 15 min, and then 1 g of sublimated sulfur was slowly added and stirred for 30 min to obtain a mixed solution of ammonium molybdate and sublimated sulfur. 3 g of urea (nitrogen source), 0.5 g of ascorbic acid (reducing agent) and 2 g of blast furnace slag (iron source, passed through a 180-240 mesh sieve) were weighed and added to the mixed solution of ammonium molybdate and sublimated sulfur in turn, ultrasonically heated to 110°C, stirred for 30 min to dissolve, and a mixed solution 1 was obtained. The mixed solution 1 was placed in a high-pressure reactor at 140°C and a pressure of 3.5 MPa for 4 h. After the reaction was completed, the mixture was centrifuged, the precipitate was collected and dried in a vacuum at 110°C, and then placed in a constant temperature zone of a tubular furnace and calcined at 600°C for 2 h. The heating program of the tubular furnace was: a rate of 10°C / min and a N2 flow rate of 20 mL / min to obtain MoS2 / Fe porous conductive particles.

[0046] 2. Preparation of polymer composite precursors

[0047] Weigh 1 g of the MoS2 / Fe porous conductive particles obtained in step 1, 1 mL of polydimethylsiloxane (PDMS) and 1 mL of ethylene glycol diacetate, respectively, and introduce them into a vacuum mixer, and stir at 1200 r / min for 30 min to obtain a polymer composite material precursor.

[0048] 3. Preparation of electrocatalyst materials

[0049] 2.5 mL of the above-mentioned polymer composite material precursor, 2.5 mL of polyacrylamide (PAM, mass fraction of 1‰), and 2.5 mL of polytetrafluoroethylene (PTFE, mass fraction of 20%) were heated to 60°C and ultrasonically oscillated for 10 min to ensure that the materials were fully mixed to obtain a microemulsion; the microemulsion was moved into a microwave drying oven, dried for 2 h at 1100 W, 120°C, and an Ar gas flow rate of 5 L / min, and then quickly placed in a freeze drying oven, freeze-dried for 20 min at 1200 W and -12°C to obtain the electrocatalyst material prepared by the present invention.

[0050] Attached Figure 1 This is a scanning electron microscope image of the electrocatalyst material prepared in Example 1 of the present invention. Figure 1 It can be seen that the electrocatalyst material prepared by the present invention has a unique cross-linked filament structure, which is formed by interweaving PAM and PDMS to form a stable cross-linked network; a large number of particles are evenly loaded on the surface of the filament structure, which provides more transmission channels and reaction sites for oxygen, which is conducive to the electrochemical reaction, thereby improving the electrocatalytic H2O2 production performance of the material. The specific surface area of ​​the electrocatalyst material is 1800 g / cm 2 The porosity is 75%, the average pore size is 0.14 μm, and the pore volume is 0.15 g / cm 3 .

[0051] In summary, this example successfully prepared an electrocatalyst material with excellent H2O2 production performance. The material exhibited good hydrophilicity, electron transfer performance and medium transport performance in the electrochemical reaction, providing new ideas and methods for the development of the electrocatalysis field.

[0052] Example 2

[0053] This embodiment provides an electrocatalyst material for in-situ production of hydrogen peroxide by oxygen reduction, and the specific preparation process is as follows:

[0054] 1. Preparation of MoS 2 / Fe porous conductive particles

[0055] 600 mg of ammonium molybdate was dispersed in 100 mL of deionized water, stirred for 15 min, and then 5 g of sublimated sulfur was slowly added and stirred for 30 min to obtain a mixed solution of ammonium molybdate and sublimated sulfur. 5 g of urea (nitrogen source), 3.5 g of ascorbic acid (reducing agent) and 10 g of blast furnace slag (iron source, passed through a 180-240 mesh sieve) were weighed and added to the mixed solution of ammonium molybdate and sublimated sulfur, ultrasonically heated to 110°C, stirred for 30 min to dissolve, and a mixed solution 1 was obtained. The mixed solution 1 was placed in a high-pressure reactor and reacted at 140°C and a pressure of 3.5 MPa for 4 h. After the reaction was completed, the mixture was centrifuged, the precipitate was collected and dried in vacuum at 110°C, and then placed in a constant temperature zone of a tubular furnace and calcined at 600°C for 2 h. The heating program of the tubular furnace was: a rate of 10°C / min and a N2 flow rate of 20 mL / min, and MoS2 / Fe porous conductive particles were obtained.

[0056] 2. Preparation of polymer composite precursors

[0057] Weigh 3 g of the MoS2 / Fe porous conductive particles obtained in step 1, 3 mL of polydimethylsiloxane (PDMS) and 6 mL of ethylene glycol ether into a vacuum mixer and stir at 1200 r / min for 30 min to obtain a polymer composite material precursor.

[0058] 3. Preparation of electrocatalyst materials

[0059] 3 mL of the above-mentioned polymer composite material precursor, 5 mL of polyacrylamide (PAM, mass fraction of 1‰), and 6 mL of polytetrafluoroethylene (PTFE, mass fraction of 30%) were heated to 60°C and ultrasonically vibrated for 10 min to ensure that the materials were fully mixed to obtain a microemulsion; the microemulsion was moved into a microwave drying oven, dried for 2 h at 1100 W, 120°C, and an Ar gas flow rate of 5 L / min, and then quickly placed in a freeze drying oven, freeze-dried for 20 min at 1200 W and -12°C to obtain the electrocatalyst material prepared by the present invention.

[0060] Attached Figure 2 This is a photo of the electrocatalyst material prepared in Example 2 of the present invention. Figure 2 It can be seen that the surface of the electrocatalyst is uniformly rough. The uniformly distributed rough structure on the surface of the material increases its surface area, providing more adsorption sites for oxygen molecules. Oxygen molecules are more likely to stay on the surface of the material and adsorb. This adsorption effect is crucial for electrocatalytic reactions because it can promote effective contact between oxygen molecules and the active sites of the catalyst, thereby improving the performance of H2O2 production; the rough surface structure also helps to improve the stability of the catalyst, which can reduce the detachment and agglomeration of the catalyst during the reaction. The specific surface area of ​​the electrocatalyst material is 3200 g / cm 2The porosity is 90%, the average pore size is 3.5 μm, and the pore volume is 0.65 g / cm 3 .

[0061] In summary, the electrocatalyst material prepared in this embodiment has a uniform and rough surface property, which provides favorable conditions for the in-situ adsorption of oxygen. This property not only improves the rate and energy efficiency of the electrocatalytic reaction, but also enhances the stability of the catalyst.

[0062] Example 3

[0063] This embodiment provides an electrocatalyst material for in-situ production of hydrogen peroxide by oxygen reduction, and the specific preparation process is as follows:

[0064] 1. Preparation of MoS2 / Fe porous conductive particles

[0065] 500 mg of ammonium molybdate was dispersed in 80 mL of deionized water, stirred for 15 min, and then 2 g of sublimated sulfur was slowly added and stirred for 30 min to obtain a mixed solution of ammonium molybdate and sublimated sulfur. 2.5 g of urea, 1.5 g of ascorbic acid and 4 g of blast furnace slag (passed through a 180-240 mesh sieve) were weighed and added to the mixed solution of ammonium molybdate and sublimated sulfur, ultrasonically heated to 110°C, stirred for 30 min to dissolve, and a mixed solution 1 was obtained. The mixed solution 1 was placed in a high-pressure reactor at 140°C and a pressure of 3.5 MPa for 4 h. After the reaction was completed, the mixture was centrifuged, the precipitate was collected and dried in a vacuum at 110°C, and then placed in a constant temperature zone of a tubular furnace and calcined at 600°C for 2 h. The heating program of the tubular furnace was: a rate of 10°C / min and a N2 flow rate of 20 mL / min to obtain MoS2 / Fe porous conductive particles.

[0066] 2. Preparation of polymer composite precursors

[0067] Weigh 4.5 g of the MoS2 / Fe porous conductive particles obtained in step 1, 10 mL of polydimethylsiloxane (PDMS) and 16 mL of ethylene glycol oxalate into a vacuum mixer and stir at 1200 r / min for 30 min to obtain a polymer composite material precursor.

[0068] 3. Preparation of electrocatalyst materials

[0069] 7 mL of the above polymer composite precursor, 7 mL of polyacrylamide (PAM, mass fraction of 5‰), and 15 mL of polytetrafluoroethylene (PTFE, mass fraction of 60%) were heated to 60°C and ultrasonically vibrated for 10 min to ensure that the materials were fully mixed to obtain a microemulsion; the microemulsion was moved into a microwave drying oven, dried for 2 h at 1100 W, 120°C, and an Ar gas flow rate of 5 L / min, and then quickly placed in a freeze drying oven and freeze-dried for 20 min at 1200 W and -12°C to obtain the electrocatalyst material prepared by the present invention. Among them, the specific surface area of ​​the electrocatalyst material is 2800 g / cm 2 , the hydrophilic angle is 65°, the porosity is 85%, the average pore size is 0.30 μm, and the pore volume is 0.40 g / cm 3 .

[0070] Example 4

[0071] This embodiment provides an electrocatalyst material for in-situ production of hydrogen peroxide by oxygen reduction, and the specific preparation process is as follows:

[0072] 1. Preparation of MoS2 / Fe porous conductive particles

[0073] 400 mg of ammonium molybdate was dispersed in 80 mL of deionized water, stirred for 15 min, and then 2.5 g of sublimated sulfur was slowly added and stirred for 30 min to obtain a mixed solution of ammonium molybdate and sublimated sulfur. 3 g of urea, 2 g of ascorbic acid and 3.5 g of blast furnace slag (passed through a 180-240 mesh sieve) were weighed and added to the mixed solution of ammonium molybdate and sublimated sulfur, ultrasonically heated to 110°C, stirred for 30 min to dissolve, and a mixed solution 1 was obtained. The mixed solution 1 was placed in a high-pressure reactor at 140°C and a pressure of 3.5 MPa for 4 h. After the reaction was completed, it was centrifuged, the precipitate was collected and dried in a vacuum at 110°C, and then placed in a constant temperature zone of a tubular furnace and calcined at 600°C for 2 h. The heating program of the tubular furnace was: a rate of 10°C / min and a N2 flow rate of 20 mL / min, and MoS2 / Fe porous conductive particles were obtained.

[0074] 2. Preparation of polymer composite precursors

[0075] Weigh 4 g of the MoS2 / Fe porous conductive particles obtained in step 1, 12 mL of polydimethylsiloxane (PDMS) and 15 mL of ethylene glycol ether into a vacuum mixer and stir at 1200 r / min for 30 min to obtain a polymer composite material precursor.

[0076] 3. Preparation of electrocatalyst materials

[0077] Heat 7 mL of the above polymer composite precursor, 10 mL of polyacrylamide (PAM, mass fraction of 5‰), and 15 mL of polytetrafluoroethylene (PTFE, mass fraction of 60%) to 60°C, and ultrasonically vibrate for 10 min to ensure that the materials are fully mixed to obtain a microemulsion; move the microemulsion into a microwave drying oven, dry it for 2 h at 1100 W, 120°C, and an Ar gas flow rate of 5 L / min, and then quickly put it into a freeze drying oven, freeze-dry it at 1200 W, -12°C for 20 min to obtain the electrocatalyst material prepared by the present invention. The electrocatalyst material prepared by the present invention is obtained. Among them, the specific surface area of ​​the electrocatalyst material is 2500 g / cm 2 , the hydrophilic angle is 70°, the porosity is 80%, the average pore size is 0.25 μm, and the pore volume is 0.38 g / cm 3 .

[0078] Example 5

[0079] This embodiment provides an electrocatalyst material for in-situ production of hydrogen peroxide by oxygen reduction, and the specific preparation process is as follows:

[0080] 1. Preparation of MoS2 / Fe porous conductive particles

[0081] 500 mg of ammonium molybdate was dispersed in 80 mL of deionized water, stirred for 15 min, and then 2 g of sublimated sulfur was slowly added and stirred for 30 min to obtain a mixed solution of ammonium molybdate and sublimated sulfur. 2.5 g of urea, 1.5 g of ascorbic acid and 4 g of blast furnace slag (passed through a 180-240 mesh sieve) were weighed and added to the mixed solution of ammonium molybdate and sublimated sulfur, ultrasonically heated to 70°C, stirred for 30 min to dissolve, and a mixed solution 1 was obtained. The mixed solution 1 was placed in a high-pressure reactor at 100°C and a pressure of 2 MPa for 2 h. After the reaction was completed, the mixture was centrifuged, the precipitate was collected and vacuum dried at 80°C, and then placed in a constant temperature zone of a tubular furnace and calcined at 400°C for 2 h. The heating program of the tubular furnace was: a rate of 10°C / min and a N2 flow rate of 20 mL / min to obtain MoS2 / Fe porous conductive particles.

[0082] 2. Preparation of polymer composite precursors

[0083] Weigh 4.5 g of the MoS2 / Fe porous conductive particles obtained in step 1, 10 mL of polydimethylsiloxane (PDMS) and 16 mL of ethylene glycol oxalate into a vacuum mixer and stir at 1200 r / min for 30 min to obtain a polymer composite material precursor.

[0084] 3. Preparation of electrocatalyst materials

[0085] 7 mL of the above polymer composite precursor, 7 mL of polyacrylamide (PAM, mass fraction of 5‰), and 15 mL of polytetrafluoroethylene (PTFE, mass fraction of 60%) were heated to 40°C and ultrasonically vibrated for 20 min to ensure that the materials were fully mixed to obtain a microemulsion; the microemulsion was transferred to a microwave drying oven, dried for 0.5 h at 500 W, 80°C, and an Ar gas flow rate of 5 L / min, and then quickly placed in a freeze drying oven, freeze-dried for 10 min at 500 W and -12°C to obtain the electrocatalyst material prepared by the present invention. Among them, the specific surface area of ​​the electrocatalyst material is 2000 g / cm 2 The hydrophilic angle is 69°, the porosity is 80%, the average pore size is 0.18 μm, and the pore volume is 0.20 g / cm 3 .

[0086] Example 6

[0087] This embodiment provides an electrocatalyst material for in-situ production of hydrogen peroxide by oxygen reduction, and the specific preparation process is as follows:

[0088] 1. Preparation of MoS2 / Fe porous conductive particles

[0089] 500 mg of ammonium molybdate was dispersed in 80 mL of deionized water, stirred for 15 min, and then 2 g of sublimated sulfur was slowly added and stirred for 30 min to obtain a mixed solution of ammonium molybdate and sublimated sulfur. 2.5 g of urea, 1.5 g of ascorbic acid and 4 g of blast furnace slag (passed through a 180-240 mesh sieve) were weighed and added to the mixed solution of ammonium molybdate and sublimated sulfur, ultrasonically heated to 110°C, stirred for 30 min to dissolve, and a mixed solution 1 was obtained. The mixed solution 1 was placed in a high-pressure reactor at 140°C and a pressure of 6 MPa for 5 h. After the reaction was completed, the mixture was centrifuged, the precipitate was collected and dried in vacuum at 110°C, and then placed in a constant temperature zone of a tubular furnace and calcined at 600°C for 3 h. The heating program of the tubular furnace was: a rate of 10°C / min and a N2 flow rate of 20 mL / min to obtain MoS2 / Fe porous conductive particles.

[0090] 2. Preparation of polymer composite precursors

[0091] Weigh 4.5 g of the MoS2 / Fe porous conductive particles obtained in step 1, 10 mL of polydimethylsiloxane (PDMS) and 16 mL of ethylene glycol oxalate into a vacuum mixer and stir at 1200 r / min for 30 min to obtain a polymer composite material precursor.

[0092] 7 mL of the above polymer composite precursor, 7 mL of polyacrylamide (PAM, mass fraction of 5‰), 15 mL of polytetrafluoroethylene (PTFE, mass fraction of 60%) were heated to 60°C, ultrasonically heated to 80°C, and ultrasonically oscillated for 40 minutes to ensure that the materials were fully mixed to obtain a microemulsion; the microemulsion was moved into a microwave drying oven, dried for 2 hours at 1500 W, 150°C, and an Ar gas flow rate of 20 L / min, and then quickly placed in a freeze drying oven, freeze-dried for 20 minutes at 1200 W and -20°C to obtain the electrocatalyst material prepared by the present invention. Among them, the specific surface area of ​​the electrocatalyst material is 2500 g / cm 2 The hydrophilic angle is 72°, the porosity is 89%, the average pore size is 0.27 μm, and the pore volume is 0.37 g / cm 3 .

[0093] Example 7

[0094] This embodiment provides an electrocatalyst material for in-situ production of hydrogen peroxide by oxygen reduction, and the specific preparation process is as follows:

[0095] 1. Preparation of MoS2 / Fe porous conductive particles

[0096] 500 mg of ammonium molybdate was dispersed in 80 mL of deionized water, stirred for 15 min, and then 2 g of sublimated sulfur was slowly added and stirred for 30 min to obtain a mixed solution of ammonium molybdate and sublimated sulfur. 2.5 g of urea, 1.5 g of ascorbic acid and 4 g of blast furnace slag (passed through a 180-240 mesh sieve) were weighed and added to the mixed solution of ammonium molybdate and sublimated sulfur, ultrasonically heated to 110°C, stirred for 30 min to dissolve, and a mixed solution 1 was obtained. The mixed solution 1 was placed in a high-pressure reactor at 120°C and a pressure of 4 MPa for 4 h. After the reaction was completed, the mixture was centrifuged, the precipitate was collected and dried in vacuum at 110°C, and then placed in a constant temperature zone of a tubular furnace and calcined at 500°C for 2 h. The heating program of the tubular furnace was: a rate of 10°C / min and a N2 flow rate of 20 mL / min to obtain MoS2 / Fe porous conductive particles.

[0097] 2. Preparation of polymer composite precursors

[0098] Weigh 4.5 g of the MoS2 / Fe porous conductive particles obtained in step 1, 10 mL of polydimethylsiloxane (PDMS) and 16 mL of ethylene glycol oxalate into a vacuum mixer and stir at 1200 r / min for 30 min to obtain a polymer composite material precursor.

[0099] 3. Preparation of electrocatalyst materials

[0100] 7 mL of the above polymer composite precursor, 7 mL of polyacrylamide (PAM, mass fraction of 5‰), and 15 mL of polytetrafluoroethylene (PTFE, mass fraction of 60%) were heated to 70°C and ultrasonically vibrated for 30 min to ensure that the materials were fully mixed to obtain a microemulsion; the microemulsion was transferred to a microwave drying oven, dried for 1 h at 1000 W, 110°C, and an Ar gas flow rate of 20 L / min, and then quickly placed in a freeze drying oven and freeze-dried for 15 min at 1000 W and -15°C to obtain the electrocatalyst material prepared by the present invention. Among them, the specific surface area of ​​the electrocatalyst material is 3100 g / cm 2 The hydrophilic angle is 65°, the porosity is 89%, the average pore size is 3.2 μm, and the pore volume is 0.60 g / cm 3 .

[0101] 2. Performance Test Experiment

[0102] On the basis of Examples 1 to 7, the contact angle of the material of the present invention was measured by using a contact angle tester (OCA25 from Ataphysics, Germany). First, the electrocatalyst material and the traditional carbon-based electrocatalyst material (commercial activated carbon fiber and commercial graphite felt, purchased from Shanghai Qijie Carbon Co., Ltd.) were placed flat and pressed on a workbench, respectively. The amount of droplets was adjusted using a microinjector to form droplets on the needle tip. The surface of the electrocatalyst material was then brought into contact with the droplets. After the droplets were clearly displayed by adjusting the workbench and the camera system, the angle formed by the droplets and the material surface was observed to obtain the contact angle data. The same test was performed on the electrocatalyst material prepared in Example 3 of the present invention, as well as the commercial activated carbon fiber material and graphite felt material for comparison, see Attachment 1. Figure 3 .

[0103] By the attached Figure 3 The data show that the contact angle of the electrocatalyst material prepared in Example 3 of the present invention is 65°, and compared with commercial activated carbon fiber materials and graphite felt materials (125° and 130°), the electrocatalyst material prepared in the present invention is more hydrophilic than traditional carbon-based electrocatalyst materials. The electrocatalyst material prepared in the present invention has excellent hydrophilicity, and the presence of the catalytic active layer makes the surface of the material more hydrophilic, which is conducive to the infiltration and penetration of the electrocatalyst material, and further facilitates the mass transfer efficiency between the oxygen in the solution and the electrocatalyst material during the reaction process, thereby improving the efficiency of oxygen reduction to produce H2O2.

[0104] The electrocatalyst material prepared in Example 3 of the present invention and the conventional carbon-based electrocatalyst material (commercial carbon felt material, commercial activated carbon fiber and commercial graphite felt purchased from Shanghai Qijie Carbon Co., Ltd.) were used as cathodes (electrode area 10 cm 2), the common metal electrode titanium plate in the market is used as the anode (electrode area 10 cm 2 The electrocatalyst material prepared by the present invention was compared with commercial carbon-based materials (including carbon felt, activated carbon fiber and graphite felt). The oxygen reduction in situ H2O2 production experiment was carried out for two hours. The H2O2 production was observed and recorded. The specific results are shown in the attached Figure 4 .

[0105] By the attached Figure 4 The data show that during the two-hour oxygen reduction reaction, the H2O2 production of the electrocatalyst material prepared by the present invention reached 1142 mg / L. Compared with the H2O2 production of the other three materials (55 mg / L 98 mg / L 118 mg / L), the electrocatalyst material prepared by the present invention has shown a significant advantage in the production of H2O2. This is due to its unique catalytic performance and optimized structure, which makes the oxygen reduction reaction on the electrode surface more efficient.

[0106] Furthermore, the electrocatalyst material prepared by Example 3 of the present invention and the conventional carbon-based electrocatalyst material (commercial carbon felt material, commercial activated carbon fiber and commercial graphite felt purchased from Shanghai Qijie Carbon Co., Ltd.) were respectively the cathode (electrode area 20 cm 2 ), the common metal electrode titanium plate in the market is the anode (electrode area 20 cm 2 , purchased from Shaanxi Baoji Yongji Metal Technology Co., Ltd.), the electrode spacing was 3 cm, 3.5 g of sodium sulfate was added to 500 mL of organic wastewater discharged from a chemical plant (phenol wastewater discharged from a chemical plant in Shaanxi), ferrous sulfate (2.5 mmol, 0.38 g) was added, the potential was 5 v, the electrocatalyst cathode material prepared by the present invention and commercial cathode materials (carbon felt, activated carbon fiber and graphite felt) were respectively subjected to 120 min advanced oxidation removal of chemical oxygen demand (COD) experiments, and the COD removal rate was observed and recorded. For details, see the attached Figure 5 As shown. Figure 5 The data show that the use of the electrocatalyst cathode material prepared by the present invention to treat organic wastewater achieved a COD removal rate of 98%. Compared with commercial cathodes (carbon felt, activated carbon fiber and graphite felt, purchased from Shanghai Qijie Carbon Co., Ltd.), the COD removal rate was only 18.5%. It can be seen that the electrocatalyst cathode material prepared by the present invention shows significant advantages in removing COD from organic wastewater, and the treatment efficiency is much higher than that of commercial cathode materials, which proves the high efficiency of the electrocatalyst material prepared by the present invention in treating organic wastewater, and it has broad application prospects in the field of chemical wastewater treatment.

[0107] Furthermore, the reusability test of the electrocatalyst material prepared by the present invention was carried out. The electrocatalyst prepared by Example 3 of the present invention and the commercial graphite felt material were used as the cathode (electrode area 8 cm 2 , purchased from Shanghai Qijie Carbon Company), the common metal electrode titanium mesh on the market is used as the anode (electrode area 8 cm 2 , purchased from Shaanxi Baoji Yongji Metal Technology Co., Ltd.), the electrode spacing was 3 cm, 3.5 g of sodium sulfate was added to 500 mL of organic wastewater discharged from a chemical plant (phenol wastewater discharged from a chemical plant in Shaanxi), 0.38 g of ferrous sulfate was added, the potential was 5 V, and the advanced oxidation removal of COD was repeated 9 times. Figure 6 The data show that the electrocatalyst cathode material prepared in Example 3 of the present invention is capable of treating organic wastewater with high efficiency for a long time, and can maintain stable performance in 9 consecutive wastewater treatment experiments.

[0108] In summary, the electrocatalyst material prepared by the present invention is used for advanced oxidation treatment of organic wastewater, which can effectively improve the treatment effect by increasing the H2O2 production and can operate efficiently and stably. The electrocatalyst material prepared by the present invention is simple to operate and can be industrialized, promoted and applied.

[0109] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing an electrocatalyst material for in-situ production of hydrogen peroxide by oxygen reduction, characterized in that: include: S1, preparation of MoS2 / Fe porous conductive particles; S2, stirring and mixing MoS2 / Fe porous conductive particles, polydimethylsiloxane and ethylene glycol to obtain a polymer composite material precursor; the mass ratio of the MoS2 / Fe porous conductive particles, polydimethylsiloxane and ethylene glycol is 1-3:1-3:1-6; S3, adding polyacrylamide and polytetrafluoroethylene to a polymer composite precursor, heating, and ultrasonic treatment to obtain a microemulsion; the volume ratio of the polyacrylamide, polytetrafluoroethylene, and the polymer composite precursor is 1-3:1-5:1-6, the heating temperature is 40°C-80°C, and the ultrasonic oscillation is 10 min-40 min; S4, the microemulsion is sequentially microwave dried and freeze-dried to obtain an electrocatalyst material for in-situ production of hydrogen peroxide by oxygen reduction.

2. The method for preparing an electrocatalyst material for in-situ production of hydrogen peroxide by oxygen reduction according to claim 1, characterized in that: In S1, the preparation of MoS2 / Fe porous conductive particles includes: dissolving and mixing ammonium molybdate and sublimated sulfur, adding a nitrogen source, a reducing agent and blast furnace slag, and then placing them in a reactor for reaction, centrifuging, drying and calcining to obtain MoS2 / Fe porous conductive particles; the nitrogen source is any one of urea, ammonium salt and nitrate, and the reducing agent is any one of ascorbic acid, hydroxylamine hydrochloride and sodium citrate; the mass ratio of ammonium molybdate to sublimated sulfur, nitrogen source, reducing agent and blast furnace slag is 0.2~0.6:1~5:3~5:0.5~3.5:2~10; the reaction temperature is 100℃~140℃, the reaction time is 2 h~5 h, and the reaction pressure is 2 MPa~6 MPa; the calcination temperature is 400℃~600℃, and the calcination time is 1 h~3 h.

3. The method for preparing an electrocatalyst material for in-situ production of hydrogen peroxide by oxygen reduction according to claim 2, characterized in that: The nitrogen source is urea, and the reducing agent is ascorbic acid.

4. The method for preparing an electrocatalyst material for in-situ production of hydrogen peroxide by oxygen reduction according to claim 2, characterized in that: The calcination was carried out using a tubular furnace with a heating rate of 10°C / min and a N2 flow rate of 20 mL / min.

5. The method for preparing an electrocatalyst material for in-situ production of hydrogen peroxide by oxygen reduction according to claim 1, characterized in that: The mass fraction of the polyacrylamide is 1‰~5‰.

6. The method for preparing an electrocatalyst material for in-situ production of hydrogen peroxide by oxygen reduction according to claim 1, characterized in that: The mass fraction of the polytetrafluoroethylene is 20% to 60%.

7. The method for preparing an electrocatalyst material for in-situ production of hydrogen peroxide by oxygen reduction according to claim 1, characterized in that: In S4, microwave drying is carried out under the conditions of Ar gas flow rate of 5 L / min~20 L / min, microwave power of 500 W~1500 W, and temperature of 80 ℃~150 ℃ for 0.5 h~2 h.

8. The method for preparing an electrocatalyst material for in-situ production of hydrogen peroxide by oxygen reduction according to claim 1, characterized in that: In S4, the freeze-drying conditions are: 500 W~1200 W, freeze-drying at -20℃~-10℃ for 10 min~20 min.

9. An electrocatalyst material for in-situ production of hydrogen peroxide by oxygen reduction prepared by the preparation method according to any one of claims 1 to 8.

10. The use of the electrocatalyst material for in-situ production of hydrogen peroxide by oxygen reduction according to claim 9 in the degradation of organic wastewater, characterized in that: The electrocatalyst material for in-situ production of hydrogen peroxide by oxygen reduction serves as a cathode.

Citation Information

Patent Citations

  • Encapsulated cathode active material particles, lithium secondary batteries containing same, and method of manufacturing

    CN110720153A

  • Visible-light-responsive composite catalytic hydrogel and preparation method thereof

    CN112439457A